A Gaussian surrogate model for residual stresses induced by orbital multi-pass TIG welding. (15th April 2017) - Portelette, Luc; Roux, Jean-Christophe; Robin, Vincent; Feulvarch, Eric
Highlights: The surrogate model proposed is entirely numerical. The surrogate model has the ability to calculate residual stresses in a multi-pass weld joint. The proposed approach is based on the Gaussian process in non-linear structural mechanics. Abstract: A surrogate model is developed for the mechanical analysis of welded steel pipes. The objective is to build a simple and fast model for calculating residual stresses as a function of the dimensions and the welding parameters. This model is based on numerical experiments which are made of multi-physical finite element simulations. First, the analysis of variance is used to attest the great influence of the input parameters. Then, the polynomial approach and the Gaussian process are compared for calculating the residual hoop stresses. Experience shows that the Gaussian process can be very successful for non-linear multi-physical welding applications.